2023
DOI: 10.2196/39128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mobile Mindfulness Meditation on the Mental Health of University Students: Systematic Review and Meta-analysis

Abstract: Background Mobile mindfulness meditation (MMM) is a mindfulness meditation intervention implemented using mobile devices such as smartphones and apps. MMM has been used to help manage the mental health of university students. Objective This study aims to evaluate the effectiveness of MMM on the mental health of university students in the areas of stress, anxiety, depression, mindfulness, well-being, and resilience. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 75 publications
(180 reference statements)
0
7
0
Order By: Relevance
“…Reangsing et al ( 64 ) conducted a systematic review with university students and observed that online MBIs improved their depressive symptoms. Chen et al ( 65 ) also reported that mobile mindfulness meditation (MMM) groups were more effective than control interventions at decreasing stress and alleviating anxiety. However, there was no difference in depression scores between the MMM and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Reangsing et al ( 64 ) conducted a systematic review with university students and observed that online MBIs improved their depressive symptoms. Chen et al ( 65 ) also reported that mobile mindfulness meditation (MMM) groups were more effective than control interventions at decreasing stress and alleviating anxiety. However, there was no difference in depression scores between the MMM and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, physical activity is linked to wellbeing (Firth et al, 2020;Lee et al, 2012;Sabe et al, 2022) and can improve and prevent symptoms of depression (Choi et al, 2019), anxiety, and psychological distress (Singh et al, 2023). Taking notice and being present (e.g., prac�cing mindfulness) seems to give several wellbeing benefits like reduced stress and anxiety (Chen et al, 2023;Querstret et al, 2020), cogni�ve and emo�onal reac�vity (Gu et al, 2015) as well as changes in brain areas involved in modula�on of mood (Singleton et al, 2014). Learning, acquire mastery in various life skills, and exposure to novelty is associated with wellbeing and protect against stress (Heller et al, 2020;Heller et al, 2013;West et al, 2020).…”
Section: The Five Ways To Wellbeing and The 5waya Interventionmentioning
confidence: 99%
“…Cook (2009) stated that the concept of emotional intelligence was first used by Peter Salovey and John Mayer in the 1990s and was written about in a particular study by Daniel Goleman entitled -Emotional Intelligence‖ in 1995. As in line with the daily curriculum, 75 rules for living as a temporary monk, and the reflection on food above, Chen, Yang, Xiao, Xu, and Zhu (2023) wrote that Mindfulness meditation exercises affect the mental health of university students so they can regulate emotions in their study life. One of the fundamental principles in maintaining emotional intelligence is limiting desires, such as the principle of asceticism (Taneja, 2022).…”
Section: Reflection On the Relationship Of Meditation With Asceticism...mentioning
confidence: 99%